Marketing Mix Strategy Analysis and Its Effect on Sales Volume of Woven Fabrics: A Case Study of UD. Pertenunan Bintang Timur, Klungkung Regency - Novitasari, Kadek Sendi; Fitriandari, Mahayanti (Countable (Contemporary Business and Sustainability Science), 2024)
Micro, Small and Medium Enterprises are a sector of the national economy. The world of the homeland had faced the Covid-19 Pandemic which resulted in several sectors being affected, and one of them was UD. Bintang Timur Weaving, which experienced a decline in sales volume. UD. Pertenunan Bintang Timur is a business that produces woven fabrics, by applying an accurate marketing strategy using SWOT analysis and BCG matrix. Increase sales volume of woven fabrics in the case study at UD. East Star Gathering in Klungkung Regency? The purpose of this research is to analyze the marketing mix strategy to increase the sales volume of woven fabrics in the case study at UD. East Star Weaving in Klungkung Regency. This research uses purposive sampling technique by giving questionnaires to 8 informants consisting of Owners, Employees, and Consumers. Data were analyzed using SWOT analysis and BCG matrix, to find out the strengths, weaknesses, opportunities, and threats that exist, and the position of a business. The results of the SWOT analysis and the BCG matrix are known to be the position of UD. The East Star weaving for the last 2 years is in the star position, which indicates that the position of UD. Bintang Timur weaving is in high growth and high market share, and based on the weight of the value of the SWOT analysis above, Bintang Timur weaving is in Quadrant I (Growth) position where in this case UD. Bintang Timur Pertenunan has implemented a SWOT analysis, but not entirely.